Fabrication of asymmetric zinc oxide/carbon nanotubes coated polysulfone photocatalytic nanocomposite membrane for fouling mitigation. Issue 40 (29th May 2021) - Phin, Hor Yan; Sin, Jin Chung; Tan, Soon Huat; Chew, Thiam Leng; Ong, Yit Thai
Abstract: Membrane filtration is a favorable option in water reclamation from contaminated water source, nevertheless, inevitable membrane fouling which greatly shortens membrane longevity and separation efficiency. The paper aimed to mitigate the membrane fouling through the formation of an asymmetric PSF‐ZnO/CNTs photocatalytic nanocomposite membrane. Instead of direct blending the photocatalyst into polymer matrix, the asymmetric nanocomposite membrane was prepared with prior formation of a self‐assembled ZnO/CNTs photocatalyst layer through wet‐processing technique followed with coating of PSF support layer via phase inversion method. The morphology of the nanocomposite membrane was characterized to confirm the formation of the asymmetric structure. The effect of ZnO/CNTs photocatalyst loading on the pore characteristic and antifouling properties of the PSF‐ZnO/CNTs nanocomposite membrane in dye remediation were assessed. The incorporation of ZnO/CNTs layer was found to endows the membrane with ability to photodegrade methylene blue. The PSF‐ZnO/CNTs membrane with 0.038 g ZnO/CNTs photocatalyst loading (M5) showed the greatest flux recovery ratio (98.46%) and the lowest irreversible fouling ratio (1.54%) while exhibited decent water permeability about 29.99 L/m 2 h without compromise the methylene blue rejection rate (91.04%). Abstract :